1-D and 2-D coordination networks based on tetrathiacalix[4]arene derivative generated with mercury and cobalt salts - Akdas-Kilic, Huriye; Graf, Ernest; Hosseini, Mir Wais; Kyritsakas, Nathalie (Tubitak Scientific & Technological Research Council Turkey, 2022)
The combination of four iso-nicotinate appended tetrathiacalix[4]arene (TCA-1) in 1,2-alternate imposed conformation behaving as neutral tectons with Co(II)Cl(2 )and Hg(II)Cl-2, metallic salts, leads to the formation of neutral, new coordination networks. Indeed, the tetrasubstituted TCA-1 derivative leads to a 1D coordination polymer with Co(II)Cl-2, and a 2D grid-like network with, llg(IDCl2. The effect of the nature of the metal used on the dimensionality was demonstrated by X-ray diffraction studies on a single crystal.
Keywords: Molecular networks; coordination polymer; thiacalix[4]arene; X-ray structure; MOLECULAR TECTONICS; POLYMERS; DESIGN; Chemistry; Engineering